ALLERGENIC AND TOXIGENIC FUNGI IN THE COMPOST OF CULTIVATION OF Agaricus brasiliensis - DIAS, Eustáquio SOUZA; GUIMARÃES, Sandra Elisa; SIQUEIRA, Félix Gonçalves de; Silva, Romildo da; BATISTA, Luis Roberto (Scientia Agraria, 2009)
The mushrooms Agaricus bisporus and Agaricus brasiliensis are grown on substrate obtained through a composting process that involves a complex and little known microbial succession. Sporulating and rapid-growth ascomycetes, and in special Aspergillus fumigatus have been reported among the different species isolated from the A. bisporus compost, indicating that pathogenic or potentially toxigenic species can remain in the compost at the end of the pasteurization process. However, in Brazil, there are no reports of isolation and identification of fungi in the growing compost of A. brasiliensis mushrooms after the pasteurization process. This study aimed to evaluate, through serial dilution technique, the presence of contaminant fungi in two kinds of A. brasiliensis growing compost (1- sugar cane bagasse/coast-cross hay; 2- cotton residue/coast-cross hay). Species of Aspergillus, Emericella and Penicillium genera have been identified. Toxigenic fungi, as Aspergillus ochraceus, Aspergillus terreus and Penicillium oxalicum, were isolated from the formulations of growing compost of A. brasiliensis. Aspergillus fumigatus was found in both formulations; however, an intense spore production on the surface was observed in compost produced from cotton residue; which caused its use to be non-viable, for safety reasons. Considering that A. fumigatus is a human pathogen, preventive measures should be taken by workers involved in the production of compost, in order to prevent successive inhalation of spores.